Ipsilateral proximal and shaft femoral fractures - Lawson, Eric (Chin J Traumatol, 2017)
PURPOSE: To study the management and evaluate anatomical and functional outcomes of patients with ipsilateral proximal and shaft femoral fractures. METHODS: A retrospective, descriptive and analytic study lasted for ten years and a half ranging from January 1, 2005 to June 30, 2015. The following parameters were studied: epidemiology, fracture characteristics, therapeutic, anatomical and functional outcomes. The correlation between different parameters was analyzed with Fischer test. The significant threshold was defined for p value <0.05. RESULTS: Ten medical files were registered. There were 7 men and 3 women, with a sex ratio of 2.33. The average age was 46 years (range: 29–62 years). It was about traffic road accidents in all cases. Motorcycle–motorcycle and motorcycle–car collision were most frequent. Average admission delay was 7 h (range: 1.5–24 h). Left side was most reached in 8 cases. According to Garden classification, there was type III cervical fracture in 2 cases, type II in 1 case and type IV in 1 case. According to Ender classification, there was type I trochanteric fracture in 3 cases, type VI in 2 cases and type VII in 1 case. According to AO classification, there was type A shaft fracture in 6 cases (A2 in 4 cases and A3 in 2 cases), type B in 2 cases (B1 in 1 case and B2 in 1 case) and type C in 2 cases (C1 in 1 case and C2 in 1 case). Average surgical delay was 28.7 days (range: 11–61 days). For proximal femoral fracture, Moore prosthesis was used in 1 case, blade plate 130° in 2 cases, long Gamma nail in 4 cases, double screwing in 2 cases and dynamic hip screw in 1 case. For shaft femoral fracture, blade plate 95° was used in 3 cases, low compressive plate in 2 cases. Osseous contention was achieved in 4 cases with long Gamma nail and in 1 case with long blade plate 130°. Nonunion of cervical fracture was achieved in 2 cases. The average osseous healing delay was 5.14 months (range: 3–12 months) for proximal femoral fracture and 5 months (range: 3–8 months) for shaft femoral fractures. According to Friedman and Wyman criteria, functional results were good in 4 cases, average in 4 cases and bad in 2 cases. Regarding implants, healing delay showed no statistic difference between one-implant group and two-implant group (p = 0.52), and among the patients with different functional outcomes (p = 0.52). Functional outcomes showed no statistic difference between one-implant group and two-implant group (p = 0.46). CONCLUSION: Ipsilateral proximal and shaft femoral fractures are relatively uncommon in our daily activities. It is difficult to recognize proximal femoral fractures which are unnoticed. Results are generally good if the doctors take the two fractures into account in the management.